Palliative Pain Treatment in Patients with Bone Metastasis – A Review - Mikołajczak, Karolina; Ćwirko, Hanna; Garlak, Urszula (Quality in Sport, 2025)
Finding cancer metastases to the bone in cancer patients significantly worsens their prognosis and transforms them into palliative patients. Unfortunately, as they are diagnosed more frequently, the health problems that result from the appearance of such lesions are becoming more and more common. Fortunately, there are a number of treatments for bone metastases that improve quality of life and prolong patient survival. These include classic methods, such as chemotherapy, radiation therapy, and surgical approaches, but doctors can also offer an increasing number of modern treatments, such as minimally invasive surgical methods and drugs that target bone directly. This article reviews the literature reports of current treatments for bone metastases.